Back Cover: Tautomeric Molecule Acts as a "Sunscreen" for Metal Halide Perovskite Solar Cells (Angew. Chem. Int. Ed. 16/2021). Issue 16 (1st March 2021) - Wang, Yang; Zhang, Zemin; Lan, Yangjie; Song, Qian; Li, Mingzhu; Song, Yanlin
Abstract : UV light and surface defects accelerate the degradation process of perovskite solar cells (PSCs). In their Communication on page 8673, Mingzhu Li, Yanlin Song, and co‐workers utilize the tautomerism of "sunscreen" molecules under UV light illumination to protect the PSC from degradation and enable molecular defect passivation, achieving high efficiency and long‐term UV stability of PSCs.